2020
DOI: 10.3390/nano10040709
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Ex Vivo Evaluation of Nepafenac-Based Cyclodextrin Microparticles for Treatment of Eye Inflammation

Abstract: The aim of this study was to design and evaluate novel cyclodextrin (CD)-based aggregate formulations to efficiently deliver nepafenac topically to the eye structure, to treat inflammation and increase nepafenac levels in the posterior segment, thus attenuating the response of inflammatory mediators. The physicochemical properties of nine aggregate formulations containing nepafenac/γ-CD/hydroxypropyl-β (HPβ)-CD complexes as well as their rheological properties, mucoadhesion, ocular irritancy, corneal and scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Recent research on ocular formulations containing CDs include: sustained-delivery eye drops [ 90 , 91 ]; in situ gelling systems [ 92 , 93 ]; mucoadhesive hydrogels [ 94 , 95 ]; CD/drug-loaded contact lenses [ 96 , 97 ]; and micro and nanosystems [ 86 , 98 , 99 ]. Also, CD-based formulations have shown potential to treat eye posterior segment diseases, such as diabetic retinopathy and age-related macular degeneration, which are commonly treated by intravitreal drug injections [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent research on ocular formulations containing CDs include: sustained-delivery eye drops [ 90 , 91 ]; in situ gelling systems [ 92 , 93 ]; mucoadhesive hydrogels [ 94 , 95 ]; CD/drug-loaded contact lenses [ 96 , 97 ]; and micro and nanosystems [ 86 , 98 , 99 ]. Also, CD-based formulations have shown potential to treat eye posterior segment diseases, such as diabetic retinopathy and age-related macular degeneration, which are commonly treated by intravitreal drug injections [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines and other mediators play essential roles in eye inflammation. 48 In this study, we examined the secretion of two inflammatory mediators, IL-1Beta and hs- CRP, in mice treated with MOX-LPs and MOX solution to determine their inflammation or irritation effect. It was found that mice with MRSA corneal infection, which were treated with MOX LPs and MOX solution, did not show any significant increase in the serum level of these inflammatory cytokines (IL-1Beta and hs-CRP) compared to a negative control (without treatment or infection) ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The corneal epithelium, esterase, is 2.5-fold more as compared to the endothelium and stroma [86]. An example is the nepafenac prodrug, used for inflammation and the pain associated with cataract surgery [87]. This shows that lipid vesicles are compatible with the corneal epithelium and leads to enhanced solubility and ease of transportation, across the cornea.…”
Section: Strategies For Enhancing Ocular Drug Delivery Systemmentioning
confidence: 99%